Board effectiveness and board dissent: A model of the board's relationship to management and shareholders - Warther, Vincent A (Journal of Corporate Finance, 1998)
To date, there has been little modeling of the board of directors as an independent entity in the corporate finance literature. Most theoretical papers omit the board entirely and model only managers and shareholders as active players. In this paper, I model the board as an entity distinct from both management and shareholders. The analysis is based on management's power in the selection and retention of board members and it focuses on the effect of this power on the frequency of open dissent in the boardroom and the board's effectiveness in disciplining management. The model predicts behavior consistent with empirical observation and produces testable implications about the links between board compensation, structure, and information and the frequency of board dissent and the level of board effectiveness.